ANALISIS KOALISI LUKMAN EDY DAN SURYADI KHUSAINI PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU TAHUN 2013 - YULIANSYAH, HADI; ", ISHAK (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
A political party is an organized group, whose members have orientation, values and ideals are the same. Political Recruitment is the process by which individuals enroll warrant or to occupy a position. Recruitment is a two way process , and its nature can be formal or informal. Recruitment candidates are strongly associated with the selection of leadership, both internal party leadership and the broader national leadership. The coalition formation occurs at the end of the second second, at which time the Indonesian Democratic Party of Struggle has not determined what his choice would form a coalition with the party. At the end of the second second official register at the County Election Commission on Wednesday, May 29, 2013 on Pekanbaru.Lukman Edy is a young political leaders who have served at the level of the House of Representatives ( DPR RI ) 2 Riau electoral district , has held a strategic position in the CBA , the Secretary-General ( Secretary General ) and the position of Minister of Rural Development. His advancement to the Governor of Riau seats into its own political record for the Riau area on the General Election in 2013 has 5 pairs Candidates for Governor and Deputy Governor and a figure advanced young people as a candidate for governor. Suryadi Khusaini is Chairman of the Indonesian Democratic Party of Struggle ( PDI-P ), this figure had also run for vice-governor pairs with Chaidir in 2008.Keyword: Political Party, Political Recruitment, Coalition